ПРОБЛЕМЫ САМОСТОЯТЕЛЬНОЙ ПОДГОТОВКИ И ЭКСТРЕННОЙ ПЕРЕПОДГОТОВКИ СТУДЕНТОВ И УЧАЩИХСЯ ПО ФИЗИКЕ - Турсунметов, К.А.; Тургунбаев, Ф.Ю.; Холбоев, Ю.Х. (SCIENCE and SOCIETY, 2025)
The article examines problem of independent preparation, revision, and urgent retraining of students and learners in the physics course, particularly in semiconductor physics. It identifies the necessary educational materials, textbooks, electronic resources, and other supplementary teaching aids that enable students to independently and successfully master and review the physics course, especially semiconductor physics, thereby contributing to effective and competent work in the fields of technics, and technologies of energetic.